Trends and Protocols in Orthodontic Finishing: A Cross-sectional Study - Hamad Alqahtani (Journal of International Clinical Dental Research Organization, 2025)
Introduction: The finishing stage of orthodontic treatment is a crucial step toward optimizing treatment outcomes. Orthodontists tend to follow different trends and protocols to achieve their planned outcomes. This study investigated orthodontists’ preferences while finishing and detailing their cases. Materials and Methods: This cross-sectional study included a questionnaire survey of 33 multiple-choice questions. The questionnaires were shared with the participants through an online platform. Data encompassing sociodemographic status, different bracket bonding strategies, and finishing practices were collected and analyzed. In total, 257 responses were obtained. Results: Of all the responding orthodontists, 62% preferred to set the incisal edges of the upper central incisors and canines at the same level, and both preferred to be more incisal to the lateral incisors. Of all the respondents, 13% preferred to use a positioner after debonding, 72% always preferred to set the marginal ridges of the molars and premolars at the same level, and 84% preferred to finish their cases with minimal anterior overjet. Based on panoramic X-ray results, 80% of the orthodontists chose to set the roots of the maxillary and mandibular teeth at the right angle to the occlusal plane and to have them parallel to each other. Open bite cases were overcorrected by 80% of the respondents, followed by deep bite and class III cases. Conclusion: Variations were noted in the ways in which orthodontists dealt with orthodontic cases in terms of finishing and detailing. Scientific evidence-based guidelines are required to achieve optimal orthodontic results.